Phytotoxicity of leachate from closed sanitary landfill on Mung Bean Seed (Vigna radiata) / Shantakumari Rajan ... [et al.] - Zulkepli, Mohamad Hilmi Aizad; Mohd Shahid, Nadiatul Syima; Ishak, Ahmad Razali; Shafie, Farah Ayuni; Mohd Yatim, Siti Rohana; Rajan, Shantakumari (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Decomposing waste at landfills will produce a highly polluted liquid called leachate which can pose a great risk to the environment and potentially be the source of soil, groundwater and water pollution. Therefore, in order to prevent the continual toxicity of landfill leachate, toxicity assessment of potential impact of leachate towards plants is a legal necessity in some nations. In this study, leachate was characterized in addition to phytotoxicity assessment using Vigna radiata seeds as an indicator. The test concentration of leachate used were 0% (control group) 3%, 5%, 10%, 25%, 50%, 75% and 100%. Seed germination and root elongation were measured and calculated after seven days exposure. All parameters were found to be within the standards limits after treatment however concentrations of zinc, iron, ammoniacal nitrogen and cyanide were observed to increase after the leachate treatment process. Germination rate, average root length and relative growth rate were observed to decrease with the increase in leachate concentration although all parameters measured were within standard limits.